The Impact of Financial Performance and Audit Opinion on the Stock Price of Technology Companies - Wibowo, Andrea Safina; Andayani, Sari (Program Studi Akuntansi Universitas Langlangbuana Bandung, 2024)
The technology company's commitment to growth and sustainability has placed it in a favorable position for potential development on the stock exchange. This research examined how return on equity, net profit margin, debt-equity ratio, price-earnings ratio, and audit opinion influence stock prices. The study used quantitative methods and focused on companies in the technology sector listed on the Indonesian Stock Exchange (IDX) from 2020 to 2023. The analysis involved double linear regression using SPSS version 25 software. Using purposive sampling, the study selected 18 technology sector companies based on specific criteria, resulting in 72 samples for analysis. The study revealed that return on equity (ROE), price-earnings ratio (PER), and audit opinions have a significant impact on stock prices. In contrast, net profit margin (NPM) and debt-equity ratio (DER) does not impact the stock prices.